Impact of plasticizers on the physical and structural properties of concrete used in constructions (2021)
Concrete has an important presence in the construction of buildings and civil works, so its application requires taking into account the standards, technical specifications and technologies that guarantee the structural stability expected by the manufacturers of materials and builders, and that is why the use of plasticizers arises as an adjuvant to the physical and mechanical properties of concrete. The objective of this article was to highlight the importance of plasticizers in the main properties of concrete used in construction and the ideal conditions for their use; based on a qualitative and quantitative approach methodology, scientifically validated sources of information related to the subject of the study were analyzed. It was possible to demonstrate significantly favorable results with the application of plasticizers as water reducers that increase mechanical strength, provided that they are used in an adequate proportion of these additives to improve the physical properties of concrete.